The impact of DRG on resource consumption of inpatient with ischemic stroke - Wei, Anle; Ren, Jianing; Feng, Wen (Frontiers in Public Health, 2023)
Background Diagnosis-related group (DRG) payments were gradually introduced and used in 12 public hospitals in L city. Given the high incidence and burden of ischemic stroke, the study aimed to assess the impact of DRG payment reform on inpatient medical resource utilization. Methods Data were obtained from the DRG local database of the new Chinese cooperative medical program in L city. The study used interrupted time series analysis to examine changes in length of stay and medical costs before and after the reform, and also assessed changes in different subgroups. Results There were 763 and 4,731 ischemic stroke patients in tertiary hospitals and 1953 and 10,439 patients in secondary hospitals before and after the DRG payment reform, respectively. After the reform, LOS was reduced 0.047 and 0.47 days in tertiary and secondary hospitals, respectively. Medical expenses decreased by 30.189 yuan in tertiary hospitals, but those increased by 44.918 yuan in secondary hospitals monthly. For gender, the average LOS reduced by 0.462 and 0.471 days for male and female in secondary hospitals. The change in medical expenses for male patients in tertiary hospitals and female in secondary hospitals were more significant, with a decrease of 65.396 yuan and increase of 56.257 yuan. The most pronounced change in resource consumption was seen for patients aged 85 years and older, with an increase in average LOS and medical expenses by 0.394 days and 382.422 yuan in tertiary hospitals. They showed a reduction in the average LOS by 1.480 days, and increase in the average medical expenses by 133.485 yuan in secondary hospitals monthly. Regarding disease severity, the most significant changes were seen in MCC patients. The average LOS decreased by 0.197 and 0.928 days and the average medical expenses decreased by 131.526 and 21.631 yuan in tertiary and secondary hospitals, respectively. Conclusion The implementation of DRG payment system has led to a reduction in the LOS in various levels of hospitals, which would save in bed resources. However, DRG payment reform can help to control medical expenses for ultra-high cases, but it may not be useful to control the overall increase in medical expenses.